Effects of urbanization on plant species diversity in central Arizona. Issue 9 (24th March 2009) - Walker, Jason S; Grimm, Nancy B; Briggs, John M; Gries, Corinna; Dugan, Laura
Abstract : Modern urban development provides an excellent laboratory for examining the interplay among socioecological relationships. We analyzed how the rapidly urbanizing Phoenix, Arizona metropolis has affected plant species diversity and community composition at a regional scale. Species diversity and plant density probably result from abiotic sorting in undeveloped desert sites, but not in urban sites. We found that species richness at the plot scale was higher for desert as opposed to urban sites; however, the estimated total species pool in the urban ecosystem is higher than that in the desert, as a result of the increased importation of introduced species through the nursery trade. Ordination of plant communities suggests three unique groupings of species based on land‐use type of the site (desert, urban, and agriculture) and two unique groupings of urban sites based on landscaping aesthetics (mesic or xeric). We therefore recognize both bottom‐up and top‐down controls of plant biodiversity within the urban ecosystem.